Method for improving drug solubility and drug composite material with enhanced solubility
By using porous silica templates with high specific surface area and ultra-high silanol density, drug molecules are loaded into the template to form drug composites with enhanced solubility, which solves the problem of low drug solubility in the existing technology and achieves significant improvements. effects on drug solubility and offer advantages in stability and cost-effectiveness.
Patent Information
- Application Number
- CN202411494974.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art has limited applicability, low effect, stability and high cost in improving drug solubility, which is difficult to meet the needs of new drug research and development and existing drug improvement.
By using silica nanoparticles with diameters between 2 and 100nm, a porous template with high specific surface area and ultra-high silanol density is prepared, combined with a drug loading process, to load drug molecules into the template to form a drug complex with enhanced solubility Material.
It has significantly improved the solubility of the drug, and the potentially increases to two to three magnitude levels. The method is simple, high -cost, scalable, and the prepared drug composite materials show excellent stability and long -term storage.
Smart Images

Figure CN119345392A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to pharmaceutical technology, in particular to a method for improving drug solubility and a drug composite material with enhanced solubility. Background Art
[0002] According to statistics from the pharmaceutical industry, 60%-70% of drug candidates are difficult to pass clinical testing and commercialization due to low solubility. In addition, the number of insoluble drug candidates is increasing due to their lipophilic nature. Such drugs show good affinity for receptors and lipid membranes in the human body, but also face the problem of difficulty in dispersing in water. Therefore, the development of effective solubility enhancement methods is crucial for the development of new drugs and the improvement of existing drugs.
[0003] To address this critical issue, various approaches have been developed, such as chemical modification, particle size reduction, solid dispersion, lipid-based formulation, or mesoporous confinement. However, each of these approaches has its own drawbacks. Chemical modification involves changing the molecular structure of the drug and is only applicable to certain drugs. Particle size reduction achieved by mechanical force or precipitation usually only shows minor solubility enhancement. Approaches such as solid dispersion and lipid-based formulation face drug-specific limitations and stability issues. Although mesoporous structures based on inorganic materials show excellent stability, they usually have problems with incomplete drug release. Therefore, the current state-of-the-art technologies face a series of challenges, such as limited applicability, low efficacy, stability issues, and high cost. Therefore, a new generation of technologies that are universally applicable, efficient, stable, and cost-effective is needed.
[0004] It should be noted that the information disclosed in the above background technology section is only used for understanding the background of the present application, and therefore may include information that does not constitute prior art known to ordinary technicians in the field. Summary of the invention
[0005] The main purpose of the present invention is to solve the problems existing in the above-mentioned background technology and to provide a method for improving the solubility of a drug and a drug composite material with enhanced solubility.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] In a first aspect of the present invention, a method for improving drug solubility comprises the following steps:
[0008] S1. Raw material preparation: preparing colloidal silica uniformly suspended in an aqueous solution, including silica nanoparticles with a diameter between 2 and 100 nm;
[0009] S2. Preparation of high-density silanol group surface material: The silica colloidal suspension is subjected to rapid evaporation of the solvent by controlling the temperature and pressure, so that the surface retains ultra-high density of silane groups, improves the affinity of the surface to drug molecules and water, and forms a porous structure to increase the specific surface area;
[0010] S3. Drug loading: mixing the active pharmaceutical ingredient with the high-density silanol group surface material, and loading the drug molecules into the material through a drug loading process.
[0011] Furthermore, the density of silanol groups on the surface of the silica nanoparticles is 10OH / nm 2 The above is to increase the adsorption capacity of the silica nanoparticles to drug molecules.
[0012] Furthermore, in step S2, the evaporation adopts a vacuum evaporation process.
[0013] Furthermore, in step S3, the drug loading process includes grinding, pressing and baking the mixture of the active pharmaceutical ingredient and the high-density silanol group surface material.
[0014] Further, in step S3, the pressing and baking process includes placing the ground mixture into a mold and pressing it using a hydraulic press to form tablets, and then baking the tablets at an optimized temperature for a set time.
[0015] Furthermore, the active pharmaceutical ingredients include: any one or more of fenofibrate, rapamycin, diclofenac, isotretinoin, trimetidine, simvastatin, olaptine, rapaglitazone, indomethacin, felodipine, flurbiprofen, paclitaxel, docetaxel, naproxen, ibuprofen, progesterone, ketoprofen, and ramipril.
[0016] In a second aspect of the present invention, a drug composite material with enhanced solubility is prepared by the method for improving drug solubility.
[0017] The present invention has the following beneficial effects:
[0018] The present invention proposes an innovative method for improving drug solubility, which utilizes a specially prepared porous silica template with a high specific surface area and ultra-high silanol density, thereby significantly enhancing the adsorption capacity for drug molecules. By carefully controlling the size of the nanoparticles and the density of the silanol groups, the present invention can effectively adsorb drug molecules under anhydrous conditions and quickly desorb and release them under aqueous conditions, thereby significantly improving the solubility of the drug, potentially by two to three orders of magnitude. In addition, the method of the present invention is simple, cost-effective, and scalable, and the prepared drug composite material exhibits excellent stability and long-term storage, which makes it promising to become a new generation of formulation technology in the pharmaceutical industry.
[0019] The porous template of the present invention is made by using silica nanoparticles with a diameter between 2 and 100 nanometers. The high curvature convex surface of these particles helps to reduce the mutual influence between silanol groups, thereby achieving a high silanol density. By precisely controlling the evaporation of the solvent under temperature and pressure conditions, the particles are induced to aggregate and form a stable porous structure. In addition, by changing the type of solvent and the evaporation conditions, the properties of the porous template can be further regulated to meet the needs of different drug molecules.
[0020] In terms of drug loading, the present invention provides flexible methods to load drug molecules into the porous template, including injecting molten drug into the template or mixing drug powder with template powder. These methods are simple and easy to scale up, which helps to reduce costs and improve production efficiency.
[0021] In addition, the present invention has verified the effectiveness of its solubilization formula through in vitro and in vivo experiments, proving the significant advantages of its composite material in terms of dissolution rate and bioavailability. Through long-term stability testing, the present invention has demonstrated that its drug composite material can maintain its performance even after years of storage, which is crucial for the commercialization and clinical application of drugs.
[0022] The versatility of the present invention provides broad prospects for future applications in the fields of drug delivery, catalysis, controlled drug release, environmental remediation and sensor development. Its method based on physical adsorption and desorption mechanism avoids chemical modification of drug molecules, making it more widely applicable and safer. In short, the present invention provides a new drug solubility enhancement technology that is efficient, stable, economical and has wide application potential.
[0023] Other beneficial effects of the embodiments of the present invention will be further described below. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1AThe physical properties, in vitro and in vivo dissolution performance, and long-term stability of the nano-sized silica particle-based solubilization formulation PE-07 were demonstrated to be effective in improving drug solubility.
[0025] Figure 1B The solubilization effect of PE-07 formulation on 18 poorly soluble active pharmaceutical ingredients (APIs) was evaluated by UV-VIS spectroscopy, demonstrating its wide applicability and significant solubility enhancement ability on different drug molecules.
[0026] Figure 2 Schematic diagram of the adsorption isotherms and desorption kinetics and APIs on the PE-07 silica surface.
[0027] Figure 3 The effects of silanol density are experimentally evaluated, the solubilization effect of materials with different silanol densities is examined, and the energy change from API-silanol to water-silanol is measured by simulation. DETAILED DESCRIPTION
[0028] The following is a detailed description of the embodiments of the present invention. It should be emphasized that the following description is only exemplary and is not intended to limit the scope and application of the present invention.
[0029] Common silica surfaces usually have silanol groups (Si-OH). These silanol groups show affinity for both water and organic functional groups including carboxyl, carbonyl, hydroxyl and amide, which are commonly found in pharmaceutical compounds. However, the typical density of silanol groups is 4-6OH / nm 2 , has a stronger affinity for the active pharmaceutical ingredient (API) than water, causing the API to be unable to be released into water but instead to adhere to the surface.
[0030] The present invention proposes a new solubility enhancement method based on a new mechanism of adsorption and desorption on the silica surface with an ultra-high density of silanol groups, which is applicable to various drugs and has the potential to become the next generation of formulation technology. By increasing the density of silanol groups, the affinity of the material surface for both API and water is doubly enhanced. However, the increase in the interaction between the surface and water is more significant. Therefore, a surface designed to have an ultra-high density of silanols can strongly adsorb various drug molecules under anhydrous conditions. When introduced into a water environment, such a surface preferentially binds water molecules, resulting in the desorption and release of previously adsorbed drug molecules. This adsorption-desorption cycle can significantly enhance the dispersion of drug molecules in water, potentially increasing solubility by two to three orders of magnitude.
[0031] The present invention provides a method for improving drug solubility, comprising the following steps:
[0032] Step S1. Raw material preparation: prepare silica nanoparticles with a diameter between 2 and 100 nm as raw materials.
[0033] To ensure biocompatibility, silicon dioxide that is generally recognized as safe (GRAS) by the FDA can be selected as the raw material. In a preferred embodiment, the density of silanol groups on the surface of the silicon dioxide nanoparticles is 10OH / nm 2 The above is to increase the adsorption capacity of the silica nanoparticles to drug molecules.
[0034] Step S2. Preparing a porous template: dispersing the silica nanoparticles in a solvent to form a colloidal suspension, and rapidly evaporating the solvent by controlling the temperature and pressure to induce the silica nanoparticles to aggregate to form a porous matrix with a large specific surface area as a porous template.
[0035] In a preferred embodiment, in step S2, the evaporation is performed using a vacuum evaporation process.
[0036] Step S3. Drug loading: mixing the active drug ingredient with the porous template, and loading the drug molecules into the porous template through a drug loading process to form a drug composite material.
[0037] In a preferred embodiment, in step S3, the drug loading process includes grinding, pressing and baking the mixture of the active pharmaceutical ingredient and the porous template. Further, in step S3, the pressing and baking process includes placing the ground mixture into a mold and pressing it using a hydraulic press to form a tablet, and then baking the tablet at an optimized temperature for a set time.
[0038] In some embodiments, the active pharmaceutical ingredients include (but are not limited to): any one or more of fenofibrate, rapamycin, diclofenac, isotretinoin, trimetidine, simvastatin, olaptin, rapaglitazone, indomethacin, felodipine, flurbiprofen, paclitaxel, docetaxel, naproxen, ibuprofen, progesterone, ketoprofen, and ramipril.
[0039] An embodiment of the present invention further provides a drug composite material with enhanced solubility, which is prepared by the method for improving drug solubility of any of the aforementioned embodiments.
[0040] The specific embodiments and experimental verification of the present invention are further described below.
[0041] In order to obtain high silanol density while preventing interactions between neighboring silanol groups, silica nanoparticles with diameters between 2 and 100 nm are used as starting materials. These nanoparticles have a convex surface with high curvature, which effectively increases the distance between neighboring silanol groups located on the curved surface, thereby reducing their mutual influence. Starting from an initial aqueous colloidal suspension, the aggregation of these particles is induced by rapidly evaporating the solvent under precisely controlled temperature and pressure conditions. The resulting dry particles are firmly adhered to each other through Si-O-Si bonds, while the pores are able to accommodate drug molecules,
[0042] Figure 1A A nano-sized silica particle-based solubilization formulation, PE-07, is shown, which has the advantages of market competitiveness, in vivo validation, stability, and universal applicability. (a) Actual photo of PE-07 excipient and (b) microscopic TEM image, in which the nano-sized silica particles are firmly connected to form a millimeter-sized solid block. c, TEM image of the PE-07 formulation composite material, showing the incorporation of fenofibrate in the porous template filled with particles. The PE-07 formulation ibuprofen (red triangle), f, Dissolution properties of crystalline ibuprofen (blue inverted triangles) and crystalline ibuprofen (yellow circles), with equal amounts of ibuprofen in each group. f, Stability was assessed by comparing UV-VIS absorbance of the original formulation (solid line) and after storage (dashed line). Four APIs were tested: flurbiprofen (blue), ketoprofen (red), ibuprofen (black), and fenofibrate (purple). Flurbiprofen, ketoprofen, and ibuprofen were stored for six months, while fenofibrate was stored for two years.
[0043] Figure 1B The solubilization effect of 18 poorly soluble APIs was evaluated using UV-VIS spectroscopy by comparing the equilibrium concentrations of the crystalline form (black) and the PE-07 formulation (red), where the peak size of the spectrum is linearly related to the solution concentration. The measurements were performed after a dissolution period of 6 hours to ensure complete release of the API, and DI water was used as the solvent.
[0044] like Figure 1A This porous matrix, called a “template,” has a large specific surface area and an ultra-high silanol density, which can be as high as 10-30OH / nm 2 , which is 2-6 times larger than conventional mesoporous silica surfaces. The synergistic effect of large surface area and ultrahigh silanol density leads to excellent adsorption capacity for a large number of drug molecules. Drug molecules can be loaded into the porous template by a variety of methods, such as injecting molten drug into the template or mixing drug powder with template powder (Methods). By preparing the template and then loading the drug, the final drug composite is produced, such as Figure 1AThe drug composite prepared by the method of the present invention exhibits extremely high solubility in water, low production cost, and long-term stability - three key attributes of next-generation formulation technology. The exact performance and potential mechanism of the method of the present invention will be described in detail below.
[0045] To evaluate the method of the present invention, ibuprofen was incorporated as an active pharmaceutical ingredient (API) into a template constructed from 7 nm silica particles (named PE-07). The commercial ibuprofen product was then tested using in vitro and in vivo experiments. Conduct comparative analysis.
[0046] For in vitro dissolution testing, a standard dissolution test apparatus was used and pure water was used as the dissolution medium to obtain a more controlled testing environment. and the dissolution profile of the crystalline form of the API as Figure 1A The results show that the composite material of the present invention achieves rapid dissolution, with a solubility of more than 90% within the first hour, while the solubility of the crystalline API is less than 20% after 6 hours. It is worth noting that the formulation of the present invention shows a faster dissolution than the established Formulated to deliver twice the dissolution results.
[0047] In order to evaluate the in vivo effect, pharmacokinetic (PK) studies were performed using mice as test subjects (methods). Specifically, four groups of mice (6 mice in each group) were given the composite material (PE-07) of the present invention, Crystallize the API and template and then measure their plasma concentrations at different time points. Figure 1A As shown in (e), the PE-07 sample of the present invention exhibits significantly enhanced pharmacokinetic properties: when containing the same amount of API, it achieves almost The peak plasma concentration (Cmax) of the crystalline API was twice that of the crystalline API and the total exposure (i.e., area under the curve) was more than 1.5 times. These data emphasize the superior performance of the composite material of the present invention. In addition, the elevated plasma concentration was quickly reached within 15 minutes, indicating the rapid action of the composite material of the present invention. As expected, the template sample showed zero concentration because it did not contain the API.
[0048] The long-term stability of the composite materials of the present invention was also rigorously evaluated by comparing fresh samples with those that had been stored for an extended period of time. Figure 1AAs shown in (f), freshly prepared samples and samples stored for 6 months and 2 years were evaluated by dissolving them in pure water for 6 hours until a stable concentration was reached. Subsequently, the UV absorption spectrum of each solution was measured, where the peak height is directly related to the solute concentration. The results revealed a significant consistency between the freshly made samples and the samples stored for a long time, confirming the long-term stability of the composite material of the present invention.
[0049] Furthermore, the broad applicability of the method of the present invention was examined by applying it to various 18 insoluble APIs, such as Figure 1B By comparing the UV spectra, the data show that the PE-07 composite material of the present invention (ie, the template made of 7 nm nanoparticles) generally has a 10-fold to 2000-fold improvement in solubility compared to the crystalline API.
[0050] In a word, all these data confirm that the method of the present invention is not only effective and stable, but also widely applicable to various medicines. In addition, the manufacturing process relies on the technology of common practice, i.e., adjusting temperature and pressure, which are simple, scalable and cost-effective. Therefore, the technology of the present invention has the potential to become the next generation formulation platform technology.
[0051] To elucidate the potential mechanism of the solubility enhancement technology of the present invention, a series of composite samples were prepared, each of which was loaded with increasing amounts of API into the template. Each sample was then dissolved in pure water, and the amount of API dissolved from each composite was quantified. The experimental results showed that only a layer of drug molecules coated on the surface of the template dissolved in water. To ensure the broad applicability of the findings of the present invention, this analysis was performed using two different types of API, ibuprofen and fenofibrate, and the results are presented below.
[0052] Figure 2 Schematic representation of the adsorption isotherms and desorption kinetics, and of APIs on the PE-07 silica surface. Solubilized API depth plotted versus API / template mass ratio for two model APIs, ibuprofen (a) and fenofibrate (c). Tuning of the API / template ratio was achieved by modifying the amount of APIs while controlling the amount of template. The soluble API depth was calculated by dividing the dissolved API volume, measured after solubilization in water using UV-VIS spectroscopy, by the surface area of the template (Supplementary Material). Insets illustrate the adsorption of single molecules, ibuprofen (b) and fenofibrate (d), onto the convex PE-07 surface via hydrogen bonds (dashed lines) linking the APIs and Si-OH groups (highlighted in red). Annotations show the estimated molecular height calculated using the Bondi van der Waals radius. e, Kinetics of the percentage of ibuprofen released in water. Data are presented in agreement with Eq. A satisfactory logarithmic fit of the linearized form of , where the power of time is equal to 1. f, Inset illustrates the desorption of ibuprofen into aqueous medium, attributed to the competitive advantage of water (blue) for the surface.
[0053] like Figure 2 As shown in (a) and (c), despite the increase in the amount of API loaded, the amount of dissolution saturates to a certain value, and saturation occurs at 11% on the x-axis ( Figure 2 a) and 25%( Figure 2 c), corresponding to 24% and 46% by volume, respectively. These saturation points are quite different from the case where the template pore space is completely occupied, which is about 30% by volume (see SI for measurements). Therefore, it is clear that the maximum amount of soluble API contained in the template is independent of the total pore volume of the template.
[0054] To understand the practical reason for this maximum dissolution volume, the amount of dissolved API was converted to its corresponding thickness on the template surface. This was achieved by first determining the surface area of the porous template using the Brunauer-Emmett-Teller (BET) method (Methods and SI) and then dividing the dissolved API volume by this surface area. Figure 2 As shown in (a), the thickness of ibuprofen API is 1.05 nm, which is very close to the molecular height of ibuprofen molecules when adsorbed on the surface silanols, 1.35 nm. Figure 2 as shown in (b).
[0055] Similar calculations were performed for fenofibrate. Figure 2 (c) shows that it corresponds to a surface coating thickness of 0.79 nm, which again matches the molecular height of 0.855 nm when the API is adsorbed to the surface, as shown in Figure 2 It is worth noting that the two types of molecules adopt distinctly different orientations when adsorbed: ibuprofen “stands” on the surface ( Figure 2 (b)), rather than Norbert "lying flat" ( Figure 2 (d)). Despite the very different orientations of these molecules, the thicknesses obtained are always consistent with the molecular height, indicating that only the monolayer of molecules closest to the surface can be dissolved in water. This provides strong evidence for a surface adsorption mechanism.
[0056] Next, the dissolution kinetics of the water-adsorbed drug molecules were investigated. A very fast dissolution rate was observed: more than 90% of the fenofibrate API was dissolved within the first 60 seconds ( Figure 2 This rate is in stark contrast to the dissolution times of several hours typically associated with mesoporous silica formulations, as reported by Vallet-Regí (2004), suggesting a very different dissolution mechanism.
[0057] In terms of polymer adsorption, Granick has established the adsorption capacity D σ (t) follows an exponential decay model:
[0058]
[0059] The exponent β is primarily influenced by the energy difference between the solvent-surface and adsorbent-surface interactions. When β = 1, it indicates that the affinity of the surface to the solvent exceeds the affinity of the surface to the adsorbent, resulting in the surface releasing the adsorbent and attracting the solvent. In the experiments of the present invention, the drug API exhibited similar properties to short polymers. The undissolved API on the surface is consistent with the decay model, in which the dissolution kinetic power is exactly 1, as Figure 2 As shown in the illustration in (e).
[0060] While measurements of dissolution amounts and rates indicate adsorption and desorption behaviors, a firm understanding of the underlying mechanisms remains elusive. To elucidate the underlying mechanisms, first-principles density functional theory simulations were applied to capture the molecular interaction picture. The simulations revealed that in a dry environment, an ultrahigh density of silanol groups on the silica template surface can adsorb drug molecules and promote their desorption upon contact with water.
[0061] We first characterize the adsorption process in a dry environment and use ibuprofen as an example API. The volume density of ibuprofen can be estimated per nm 2 This is consistent with the density of silanol groups on the surface of typical mesoporous silica, which ranges from 4 to 6 groups per nm. 2 , with an average of about 5 groups per nm 2 . Therefore, in standard mesoporous silica, each ibuprofen molecule may form a hydrogen bond with one silanol group. According to DFT calculations, the enthalpy change generated by this one-to-one adsorption is -58.17 kJ / mol, which is insufficient to overcome the enthalpy of evaporation required to extract one ibuprofen molecule from the bulk, which is 80.3 kJ / mol. Therefore, typical mesoporous silica cannot effectively adsorb ibuprofen to form a stable composite material.
[0062] In contrast, the silica templates of the present invention feature a significantly higher density of silanol groups than normal - up to four times higher. This high density of silanol groups enhances the magnitude of the adsorption enthalpy. When an ibuprofen molecule interacts with two silanol groups, the adsorption enthalpy increases to -71 kJ / mol, close to the enthalpy of vaporization of ibuprofen. As the interactions strengthen to include three or four silanol groups per ibuprofen molecule, the adsorption enthalpies (-84.82 kJ / mol and -81.00 kJ / mol) become strong enough to exceed the enthalpy of vaporization of ibuprofen. This high density of silanol groups creates a "sticky" surface that effectively adsorbs drug molecules from the bulk to form a monolayer, as previously shown. Figure 2 The data shown in (a).
[0063] Figure 3 Figure 2 shows the experimental evaluation of the effect of silanol density, the solubilization effect of materials with different silanol densities is examined, and the energy change from API-silanol to water-silanol is measured by simulation. a, DFT-optimized (B3LYP-D3 / 6-311++G**, SMD) geometries of ibuprofen-silanol and water-silanol interactions for four silanol densities (σ_OH = 5, 10, 15, and 20 / nm^2). The silica clusters form hydrogen bonds with different numbers of silanols (dashed blue lines), with one ibuprofen molecule in the first row and two water molecules in the second row. Considering the molecular volumes of ibuprofen, water, and amorphous silica, the silanol density can be averaged in a single silica cluster as follows: σ_OH = 5 / nm^2 for an isolated silanol, σ_OH = 10 / nm^2 for a pair of twin silanols, σ_OH = 15 / nm^2 for a pair of twin silanols plus a neighboring silanol, and σ_OH = 20 / nm^2 for two pairs of twin silanols. Atoms are arranged in descending order of size, silicon (dark blue), oxygen (red), carbon (yellow), and blue (green). b, Solubilization of two APIs, ibuprofen (red) and fenofibrate (black), was evaluated using mesoporous silica materials with different σ_OH values. c, Enthalpy change from IBF-silanol to water-silanol as a function of silanol density (σ_OH) for the four silanol densities in (a). d, Concentration (dissolved API / solvent) measured by UV-VIS spectroscopy is plotted against the ratio of total API to solvent. The API used here is ibuprofen, formulated with PE-07 at a ratio of 40% API to template.
[0064] Figure 3 (a) shows the most favorable adsorption configurations at different silanol densities, ranging from one-to-one to one-to-four (ibuprofen to silanol) interactions. Therefore, ultrahigh silanol density is crucial for the stable adsorption of drug molecules to the surface to form a robust composite.
[0065] Adsorption of drug molecules to the surface is a critical initial step, but facilitating their subsequent desorption and dispersion into water is equally important. The present DFT simulations demonstrate once again that the same ultra-high silanol density that makes adsorption possible under dry conditions is also critical in an aqueous environment. When the drug composite is immersed in water, it faces a competitive situation for adsorption of drug molecules and water molecules on the silica surface, which is determined by the difference in adsorption enthalpy values. Since the area density of water is twice that of ibuprofen, it can be inferred that two water molecules should replace one ibuprofen molecule during desorption.
[0066] In the case of σΟH=5 / nm 2 On a typical silica surface, the simulations of the present invention show that the adsorption enthalpy (Hw) of two water molecules is -14.73 kJ / mol, which is weaker than the -18.76 kJ / mol of ibuprofen (HIbu) in an aqueous environment. Therefore, the enthalpy change associated with substitution, Hrep = Hw - HIbu = 4.03 kJ / mol (1.63 kBT), is positive and exceeds the thermal energy at room temperature, indicating that desorption and substitution on standard mesoporous silica is an unlikely event. This may explain why in typical silica, regardless of its pore structure, whether ordered mesoporous, microporous or aerosol, incomplete drug release is usually observed.
[0067] However, as the silanol density increases, H w and H Ibu Both are increasing, with Hw increasing more significantly. Figure 3 The detailed data in (b) show that as the silanol density σ Ο H increases, the substitution enthalpy Hrep decreases, and at about σ ΟΗ =12 / nm 2 When the dissipation k is below room temperature B This threshold indicates that at or above this silanol density, the desorption and dissolution process of ibuprofen molecules is greatly promoted. When the density reaches about 20 / nm 2 When , Hrep becomes negative, indicating that desorption and rapid dissolution are thermodynamically favored. Figure 3 The lower row of (a) shows the different molecular configurations of water molecules adsorbed at different silanol densities.
[0068] To verify the predictions derived from DFT simulations, a series of experimental studies were performed on various surfaces with different silanol densities (Methods). Two commercial mesoporous silica materials and three templates developed in this invention were used. The two commercial products are mesoporous silica materials with a density of approximately 5 / nm. 2 Mesoporous silica pharmaceutical excipients with high silanol density ( and ); The three templates developed in this invention show a higher silanol density: 12.69 / nm2 、15.01 / nm 2 and 17.34 / nm 2 To ensure the generalizability of the results of the present invention across different drugs, two different active pharmaceutical ingredients (APIs), ibuprofen and fenofibrate, were selected. The same amount of each drug was loaded into five types of silica materials using the same process. These drug composites were then dissolved in pure water, and the final dissolved fraction was measured.
[0069] Experimental results, such as Figure 3 As shown in (c), it is shown that the silanol density of a typical silicon product is 5 / nm 2 The solubility of the template of the present invention is low when the silanol density is about 12 / nm. 2 A significant increase in solubility was observed when Figure 3 (b) The replacement enthalpy (Hrep) is equal to the room temperature dissipation (k B T)'s theoretical point is consistent.
[0070] Figure 3 The solubility data in (c) are similar to Figure 3 The excellent negative correlation between the substitution enthalpies in (b) emphasizes the validity of the DFT simulation. The results clearly show that higher silanol density leads to lower substitution enthalpy, which facilitates the desorption of drug molecules and enhances drug solubility. Therefore, the solubility measurements provide strong experimental support for the DFT calculations.
[0071] In addition, the present invention reveals an additional unique advantage: since the dissolution of drug molecules from the special surface of the present invention is driven by thermodynamic substitution enthalpy, more drug composite material can be continuously added to the water to continuously increase the drug concentration. Figure 3 This is illustrated in (d): the concentration of ibuprofen can be continuously increased to three orders of magnitude higher than its crystalline form, a remarkable result that has never been seen before! Although this ultra-high concentration represents a metastable state, this state remains stable for more than 24 hours, exceeding the usual time frame for drugs to exert their effects. Therefore, the technology of the present invention provides a unique advantage by achieving ultra-high drug concentrations, a property that may find practical potential in pharmaceutical applications.
[0072] In summary, the development of silica templates with ultrahigh silanol density has significantly increased the solubility of drugs, easily achieving enhancements of two to three orders of magnitude. This advance is based on a new physical mechanism: adsorption and desorption processes inherent to these engineered silica surfaces. This fundamental mechanism avoids the need for chemical modification of drug molecules and is applicable to a wide range of drug compounds. It is also efficient, cost-effective, scalable and stable, all of which are invaluable in pharmaceutical manufacturing. Therefore, the present method has the potential to become a new generation solubility enhancement platform technology and replace multiple state-of-the-art technologies.
[0073] In addition, PE-07 provides a high density of interaction sites on the surface with its abundant stable silanol groups. These can be modified with various functional groups to accommodate a wider range of chemicals. This versatility makes it potential for application in drug delivery, catalysis, controlled drug release, environmental remediation, sensor development, etc.
[0074] Examples
[0075] Template preparation and drug loading
[0076] The templates were prepared using aqueous colloidal silica. The silica particles were nanosized, 7 nm, 12 nm, and 22 nm, corresponding to PE-07, PE-12, and PE-22. To achieve the template formation, these suspensions underwent a vacuum evaporation process at a specific temperature.
[0077] In the drug loading procedure, the following active pharmaceutical ingredients (APIs) were used: Ibuprofen Ketoprofen, flurbiprofen, docetaxel, diclofenac, repaglinide, oxaprozin, isotretinoin, rapamycin, indomethacin, naproxen, simvastatin, trimebutine, fenofibrate, ramipril, paclitaxel, progesterone and felodipine (all from J&K ).
[0078] APIs are manually ground along with appropriate templates. The ground mixture is then placed in a mold and pressed using a hydraulic press, applying a pressure of 80 MPa to form tablets. The tablets are subsequently baked at an optimized temperature for a specific time (hours). The baking process helps in the relaxation of drug molecules and promotes effective interaction between the template and APIs.
[0079] Concentration measurement
[0080] In vitro dissolution testing was performed using a homemade apparatus designed to the specifications of USP Apparatus 2, featuring a rotating blade in a cylindrical container rotating at 50 RPM. The dissolution process began with the introduction of a single tablet into 500 mL of dissolution medium. After drug release, solution samples were collected at planned intervals to evaluate dissolution kinetics. The solubility profiles of 18 active pharmaceutical ingredients (APIs) were evaluated at the 6-hour time point. It was experimentally verified that the solution had reached a stable, fully dissolved state at this time point. Thereafter, the solution was sampled using The solution samples were filtered through a 0.2 μm syringe filter and The concentration was determined using a UV / Vis spectrophotometer L850. To establish the absorbance (ε), the linear coefficient linking UV / VIS absorption to concentration, a calibration was performed by evaluating the absorption of a series of solutions of known concentrations.
[0081] Pharmacokinetic studies
[0082] A total of 24 C57BL / 6J male mice weighing 22-24 grams were used in the pharmacokinetic study. There were six mice in each of the four study groups. The study included four groups, including 20% dose PE-07 formulation ibuprofen, 98% ibuprofen crystals, 45.7% dose grind The concentrations of PE-07 formula ibuprofen and pure PE-07 template as controls were 50 mg / kg and 10 mg / kg of pure ibuprofen. 21.9 mg / kg. In addition to the control group, mice were given the same amount of active ibuprofen (10 mg / kg). After a single dose, blood was collected at the following time points: 15 minutes, 30 minutes, 1 hour, 2 hours, 4 hours, 8 hours, 24 hours. Plasma concentrations were then measured using LC / MS analysis.
[0083] Silanol density measurement
[0084] At room temperature, the silanol groups on the template surface form hydrogen bonds and are in equilibrium with each other. However, at elevated temperatures, these groups undergo condensation and dehydration reactions. This property allows the quantification of the number of silanols using thermogravimetric analysis (TGA). The number of silanols per unit mass of the template was quantified on the TGA550 system. The weight loss of the template was measured under gradually increasing temperature conditions. In order to eliminate the weight loss of water in the pores, the weight measurement started at 200°C. By measuring the weight loss in the temperature range of 200-1000°C, the majority of silanol groups present on the template surface can be quantified (results in SI).
[0085] Ibuprofen and fenofibrate were selected as model active pharmaceutical ingredients (APIs), and the templates were adjusted to investigate which properties of the templates play a dominant role in enhancing dissolution. To explore this, colloidal suspensions with particle sizes of 5 nm, 7 nm, 12 nm, and 22 nm were used to prepare four materials with different silanol surface densities, namely PE-05, PE-07, PE-12, and PE-22, and compared with commercially available silica mesoporous solubilizing excipients Syloid and Silsol. A comparative experiment was conducted, and the material properties and the effect of improving the solubility of ibuprofen and fenofibrate are shown in Table 1.
[0086] Table 1
[0087]
[0088]
[0089] The specific surface area, average pore size and porosity in Table 1 were characterized by Brunauer–Emmett–Teller (BET) analysis of nitrogen volume adsorption isotherms. The silanol surface density was calculated by thermogravimetric analysis (TGA) to measure the mass change of silicon material with temperature. The mass loss below 200°C is due to the removal of physically adsorbed water, while the mass loss above 200°C is due to the removal of surface hydroxyl groups. The Si-OH density was calculated by dividing the mass loss between 200°C and 1000°C by the specific surface area, as shown in the table. It is worth noting that all nano-sized colloidal filling templates are compared to The mesoporous silica exhibited significantly higher surface Si-OH density. In addition, the results showed that smaller template sizes corresponded to higher Si-OH density in the order of 5 nm > 7 nm > 12 nm > 22 nm.
[0090] After characterizing these five groups of silica templates, their ability to enhance the dissolution of ibuprofen and fenofibrate was compared, as shown in the table. Syloid silica showed no significant difference compared to the pure crystalline drug on both APIs. In addition, Silsol did not improve the dissolution of ibuprofen, but slightly enhanced fenofibrate, which is consistent with the results of Humbeeck's study. However, the PE series materials showed significantly better performance on both APIs, despite having lower specific surface area and porosity than Grace silica. In addition, materials with higher silanol surface density showed better performance. This finding suggests that surface characteristics play an important role in enhancing dissolution, rather than pore size, porosity or specific surface area. It can be reasonably inferred that the significant improvement in API dissolution is attributed to its interaction with the surface.
[0091] The surface silanol density can be calculated by dividing the number of silanols per unit mass by the specific surface area of the template. The specific surface area was measured by ASAP2020 (results in SI). Before the measurement, the template was stored in a vacuum oven at 120 °C overnight to remove moisture. The measurement was based on the Brunauer-Emmett-Teller (BET) method by nitrogen adsorption.
[0092] The silanol densities of PE-07, PE-12, and PE-22 were determined, as well as two typical silica types: WR Grace’s and Each has 5OH / nm 2 The silanol density is Specially designed for enhanced solubility.
[0093] First principles simulation
[0094] Ab initio simulations were performed using the Gaussian 16 software package. The calculations were performed using the B3LYP-D3 hybrid functional and the 6-311++G(d,p) basis set, which provides a good balance between computational cost and accuracy. D3 dispersion correction was applied because previous studies have shown that dispersion forces play a dominant role in the interaction between ibuprofen and silica surfaces.
[0095] The geometry of the silica clusters interacting with ibuprofen was optimized until the overall enthalpy was minimized. The enthalpy H was calculated by combining the zero-point correction (ΔZPE) and the thermal correction (ΔE T ) added to the BSSE-corrected electron energy (E c ) to calculate:
[0096] H=E c +ΔZPE+ΔE T
[0097] By calculating the enthalpy (H Ibu-Si ) minus ibuprofen (H Ibu ) and silanol clusters (H Si The adsorption enthalpy ΔH is determined by summing the enthalpies of Ibu :
[0098] ΔG Ibu =H Ibu-Si -H Ibu -H Si
[0099] Similarly, the adsorption enthalpy of water dimer on silica, ΔH w :
[0100] ΔH w =H w-Si -Hw -H Si
[0101] The adsorption process simulates the interaction of ibuprofen with silica clusters in a vacuum environment. As for the dissolution process, it is simulated in water using a density-based solvation model (SMD). This comparison involves analyzing the adsorption enthalpy of water dimer on silica and ibuprofen on silica.
[0102] The above content is a further detailed description of the present invention in combination with specific / preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, it can also make several substitutions or modifications to these described embodiments, and these substitutions or modifications should be regarded as belonging to the protection scope of the present invention. In the description of this specification, the description of the reference terms "an embodiment", "some embodiments", "preferred embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in combination with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily target the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In the absence of mutual contradiction, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples. Although the embodiments of the present invention and their advantages have been described in detail, it should be understood that various changes, substitutions and modifications can be made herein without departing from the scope of protection of the patent application.
Claims
1. A method for improving drug solubility, characterized in that: The following steps are involved: S1. Raw material preparation: preparing colloidal silica uniformly suspended in an aqueous solution, including silica nanoparticles with a diameter between 2 and 100 nm; S2. Preparation of high-density silanol group surface material: The silica colloidal suspension is subjected to rapid evaporation of the solvent by controlling the temperature and pressure, so that the surface retains ultra-high density of silane groups, improves the affinity of the surface to drug molecules and water, and forms a porous structure to increase the specific surface area; S3. Drug loading: mixing the active pharmaceutical ingredient with the high-density silanol group surface material, and loading the drug molecules into the material through a drug loading process.
2. The method for improving drug solubility according to claim 1, characterized in that: The density of the silanol groups on the surface of the silica nanoparticles is above 10 OH / nm2, so as to increase the adsorption capacity of the silica nanoparticles for drug molecules.
3. The method for improving drug solubility according to claim 1 or 2, characterized in that: In step S2, the evaporation adopts a vacuum evaporation process.
4. The method for improving drug solubility according to any one of claims 1 to 3, characterized in that: In step S3, the drug loading process includes grinding, pressing and baking the mixture of the active pharmaceutical ingredient and the high-density silanol group surface material.
5. The method for improving drug solubility according to claim 4, characterized in that: In step S3, the pressing and baking process includes placing the ground mixture into a mold and pressing it using a hydraulic press to form tablets, and then baking the tablets at an optimized temperature for a set time.
6. The method for improving drug solubility according to any one of claims 1 to 5, characterized in that: The active pharmaceutical ingredients include: any one or more of fenofibrate, rapamycin, diclofenac, isotretinoin, trimetidine, simvastatin, olaptine, rapaglitazone, indomethacin, felodipine, flurbiprofen, paclitaxel, docetaxel, naproxen, ibuprofen, progesterone, ketoprofen, and ramipril.
7. A drug composite material with enhanced solubility, characterized in that: The drug is prepared by the method for improving drug solubility as described in any one of claims 1 to 6.